3D characterisation of the dynamics of foot joints of adults during walking. Gait pattern identification. Issue 9 (4th July 2017) - Sanchis-Sales, E.; Sancho-Bru, J. L.; Roda-Sales, A.; Pascual-Huerta, J.
Abstract: A detailed description of the kinematics and kinetics of the ankle, midtarsal and metatarsophalangeal joints of the feet of a healthy adult male population during barefoot walking is provided. Plots of the angles and moments in each plane during the stance phase are reported, along with the mean and standard deviation values of 87 different parameters that characterise the 3D dynamics of the foot joints. These parameters were used to check for similarities between subjects through a hierarchical analysis that allowed three different gait patterns to be identified, most of the differences corresponding to the frontal and transverse planes.